Influence of activation on the multipoint immobilization of penicillin G acylase on macroporous silica - CARDIAS, H.C.T.; GRININGER, C.C.; TREVISAN, H.C. [UNESP]; GUISAN, J.M.; GIORDANO, R.L.C. (Brazilian Society of Chemical Engineering, 1999)
Penicillin G acylase is the second most important enzyme used by industry in an immobilized form. Penicillin hydrolysis is its main application. This reaction is used to produce 6-aminopenicillanic acid (6-APA), an intermediate in the synthesis of semisynthetic antibiotics. This work aims to compare catalytic properties of different penicillin G acylase (PGA) derivatives obtained by multipoint immobilization of the enzyme on macroporous silica. Enzyme amino groups react with different aldehyde groups produced in the support using either glutaraldehyde or glyoxyl activation. In the former method, silica reacts with g-aminopropyltriethoxysilane (g-APTS) and glutaraldehyde; in the latter, a reaction with glycidoxypropyltrimethoxysilane (GPTMS) is followed by acid hydrolysis and oxidation using sodium periodate. This work determines the influence of degree of activation, using glutaraldehyde, on immobilization parameters. PGA was immobilized on these two different supports. Maximum enzyme load, immobilized enzyme activity (derivative activity), rate of immobilization and thermal stability were checked for both cases. For glutaraldehyde activation, the results showed that 0.5% of the g-APTS is sufficient for all the hydroxyl groups in the silica to react. They also showed that degree of activation only affects immobilization yield and reaction velocity and that reduction of the glutaraldehyde derivatives with sodium borohydride does not affect their thermal stability. In comparing the derivatives obtained using glyoxyl and glutaraldehyde activation, it was observed that the glyoxyl derivatives presented better immobilization parameters, with a maximum enzyme load of 264 IU/g silica and a half-life of 20 minutes at 60 °C.
Keywords: Penicillin G; immobilization; macroporous silica